Silver‐Bismuth Based 2D Double Perovskites (4FPEA)4AgBiX8 (X = Cl, Br, I): Highly Oriented Thin Films with Large Domain Sizes and Ultrafast Charge‐Carrier Localization. Issue 14 (3rd July 2022) - Hooijer, Rik; Weis, Andreas; Biewald, Alexander; Sirtl, Maximilian T.; Malburg, Julian; Holfeuer, Rico; Thamm, Simon; Amin, Amir Abbas Yousefi; Righetto, Marcello; Hartschuh, Achim; Herz, Laura M.; Bein, Thomas
Abstract: Two‐dimensional (2D) hybrid double perovskites are a promising emerging class of materials featuring superior intrinsic and extrinsic stability over their 3D parent structures, while enabling additional structural diversity and tunability. Here, we expand the Ag–Bi‐based double perovskite system, comparing structures obtained with the halides chloride, bromide, and iodide and the organic spacer cation 4‐fluorophenethylammonium (4FPEA) to form the n = 1 Ruddlesden–Popper (RP) phases (4FPEA)4 AgBi X 8 ( X = Cl, Br, I). We demonstrate access to the iodide RP‐phase through a simple organic spacer, analyze the different properties as a result of halide substitution and incorporate the materials into photodetectors. Highly oriented thin films with very large domain sizes are fabricated and investigated with grazing incidence wide angle X‐ray scattering, revealing a strong dependence of morphology on substrate choice and synthesis parameters. First‐principles calculations confirm a direct band gap and show type Ib and IIb band alignment between organic and inorganic quantum wells. Optical characterization, temperature‐dependent photoluminescence, and optical‐pump terahertz‐probe spectroscopy give insights into the absorption and emissive behavior of the materials as well as their charge‐carrier dynamics. Overall, we further elucidate the possible reasons for the electronic and emissive properties of these intriguing materials, dominated by phonon‐coupled and defect‐mediated polaronic states. Abstract : Three silver‐bismuth‐based 2D double perovskites (4FPEA)4 AgBi X 8 ( X = Cl, Br, I) are synthesized in crystalline powder and thin film form. The highly crystalline and strongly oriented thin films are characterized, and incorporated into photodetector devices and the challenging charge‐carrier characteristics of these structures are investigated.